2018
DOI: 10.1007/s11013-018-9604-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Understanding Depression in Women in Kisoro, Uganda

Abstract: Depression is highly prevalent and the cause of considerable suffering for peoples across the globe. Case finding for depression is challenging because individuals often do not recognize the symptoms in themselves or may resist the diagnosis as a result of cultural stigma. Screening instruments, to be accurate, must be valid in the particular setting in which they are being applied, and diagnosis in primary care settings, is further made challenging because patients often present with a wide variety of somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The study in Kisoro involved women recruited from a hospital setting who had presented for care with various medical conditions and somatic symptoms. As documented in previous research individuals with somatic symptoms may have ongoing depression, and this may explain the high prevalence of depression in the Kisoro study compared to the current study where women were recruited from the community [11,36]. On the other hand, the prevalence of depression found in our study was much higher than that found in another study (38%) conducted in urban setting (Mbarara) using the Hopkins Symptom Checklist-Depression Subscale [37].…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…The study in Kisoro involved women recruited from a hospital setting who had presented for care with various medical conditions and somatic symptoms. As documented in previous research individuals with somatic symptoms may have ongoing depression, and this may explain the high prevalence of depression in the Kisoro study compared to the current study where women were recruited from the community [11,36]. On the other hand, the prevalence of depression found in our study was much higher than that found in another study (38%) conducted in urban setting (Mbarara) using the Hopkins Symptom Checklist-Depression Subscale [37].…”
Section: Discussionsupporting
confidence: 47%
“…Our study ndings show a high prevalence of depression among the study participants and a statistically signi cant association between depression and spouse extra marital affairs. The prevalence of 65% was slightly lower than that documented in a study in Kisoro (75%) another rural district in southwestern Uganda among women aged 18 to 35 years based on the Self-Reporting Questionnaire (SRQ-20) [11]. The difference may be due to the study population recruited in the two studies.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations